UPAYA MENINGKATKAN KECERDASAN INTERPESONAL ANAK USIA 5-6 TAHUN DENGAN MENGGUNAKAN METODE BERMAIN PERAN DI SPS MEKAR KARYA IV BABAKANBARU - Rosinah Rosinah; Indra Zultiar; Alpian Ashshidiki Popiariana (CV. ADIBA AISHA AMIRA, 2023)
One approach to improving children's social competence is to use the method of playing catch-up, which is chosen because it can help improve children's social competence, understanding, and self-confidence. social and social communication. This type of research is a collaborative learning study that used the Kemmis and McTaggart models. Ten students from B SPS Mekar Karya IV Babakan Baru in Kecamatan Ciracap, Kabupaten Sukabumi, consisting of five boys and five girls, are the subjects of this research. The three dimensions of social competence social empathy, social understanding, and social communicationmake up the research object here, which is children's interpersonal competence. Observation and documentation are the data collection methods used. Observation and documentation tools are utilised. Data analysis is carried out using quantitative descriptive methods. The study's success will be indicated when the percentage cutoff shows that 75% of the children experience an increase in interpersonal competence using the method of playing catch. In the presence of play, the results of the study show that children's interpersonal competence increases. The percentage of interpersonal competence revealed by the data did not change when the observation was conducted. Out of the total number of children, 2 (or 10%) met the BB criteria, 13 (or 65%) met the MB criteria, 5 (or 25%) met the 25% criteria, and 0% met the BSS criteria. After the first cycle of testing is completed, there are 2 children with 20% meeting the MB criteria, 4 children with 40% meeting the BSH criteria, 4 children with 40% meeting the BSB criteria, and in the second cycle, 1 child with 10% meeting the BSH criteria and 9 children with 90% meeting the BSB criteria undergo an increase. Tips yang ditempuh untuk meningkatkan kecerdasan anak dibandingkan dengan metode bermain peran. Activities of active support are carried out during development projects, and activities of reward are carried out during maintenance projects.